The impact of Cochrane Reviews that apply network meta-analysis in clinical guidelines: A systematic review. - Sarah Donegan; James Connor; Zarko Alfirevic; Catrin Tudur-Smith (PLoS ONE)
Background Systematic reviews, such as those prepared by Cochrane, are the strongest evidence on which to base recommendations in clinical guidelines. Network meta-analysis (NMA) can be used to combine the results of studies to compare multiple treatments, which is advantageous over pair-wise meta-analysis (PW-MA) that compares two treatments. We aimed to summarise which, when, where, who, and why Cochrane Reviews that applied NMA were cited in guidelines; and to compare the citation of NMA reviews in guidelines with PW-MA reviews. Methods and findings We carried out a systematic review of Cochrane reviews that applied NMA and we summarised their citation in guidelines. The Cochrane Database of Systematic Reviews was searched (15th January 2024). Additionally, a cohort of Cochrane reviews that applied PW-MA was matched to the NMA reviews. Two authors assessed eligibility and extracted data. We summarised review and guideline characteristics, and the use of the review in guidelines. Results Of the 60 included NMA reviews, 26 reviews (43%) were cited in 89 guidelines (1-13 per review). 15 NMA reviews (58%) were first cited within two years of publication, with the remaining 11 reviews (42%) cited 2-6 years later. 52 guideline developers authored the guidelines. The number of citations was higher for NMA than PW-MA reviews (rate ratio 1.53 (1.08 to 2.19), p = 0.02). The number of times reviews were commissioned or cited alongside a recommendation was also higher for NMA than PW-MA reviews (rate ratio 4.40 (1.80 to 13.14), p = 0.003). NMA reviews were more likely to be cited in the text surrounding a recommendation or used for NICE guideline development (1.94 (1.08 to 3.63), p = 0.03). Conclusions Cochrane NMA reviews appear to have more impact than PW-MA reviews, but many are not cited in guidelines. Further work is needed to explore the barriers to use of NMAs and promote their use.